ASSESSMENT OF THE INFLUENCE OF THE INTENSITY OF TRAFFIC FLOWS ON THE STATE OF THE STREET AND ROAD NETWORK OF THE CITY - Samoylenko Yevhen; Holodenko Viktoriia (World Science, 2024)
The article is devoted to the assessment and forecasting of the level of atmospheric air pollution in street canyons in Kyiv by controlling the parameters of traffic flow. Today, road transport is the main anthropogenic source of environmental pollution. The specificity of air pollution by traffic flows lies in their ground location, close proximity to people’s homes, which leads to the accumulation of pollutants near the ground surface - in the breathing zone of people. The article analyzes the main approaches to modeling the dispersion of pollutants in the atmosphere from motor vehicles. It is advisable to assess the level of urban air pollution in homogeneous elements of the urban area - street canyons. Based on the urban street canyons model (OSPM), the level of pollution in the street canyons of the Pechersk district of Kyiv by the main harmful substances contained in car exhaust gases is determined. The critical intensity of traffic flows for each of the street canyons at which the level of pollution by the corresponding harmful substance reaches the maximum permissible value was determined. Thus, the obtained results of the study allow us to quickly predict the level of air pollution in the roadside space of cities and prevent environmentally hazardous situations by controlling the parameters of the traffic flow.